Kertha Gosa as Restorative Justice Hall : A Law Enforcement with Social Harmony Maintenance - I Komang Bayu Segara (Bali Tourism Journal, 2022)
Legal issues have recently become a public spotlight, especially for victims involved in legal cases. To that end, the Klungkung District Attorney established the Restorative Justice Agency to reduce crime by holding a meeting between the victim and the defendant. Kertha Gosa, a historical landmark located in the middle of the city of Semarapura, has been chosen to be the center of the activity. The Kertha Gosa has served as a venue for trial since the glorious time of the Semarapura Kingdom. After the dutch invasion of Indonesia in 1908, the place continued to hold the title of hall of justice, including several functions as an educational institution for expatriates. According to its historical facts and values, a decision to make the Kertha Gosa site a restorative justice center for Klungkung regency was an excellent resolve. The Regent of Klungkung, I Nyoman Suwirta, appreciated the given status of the hall as the center to resolve crime acts. Furthermore, the Head of the Bali High Court, Ade T. Sutiawarman, expected the historical site would continue to represent law enforcement but still maintain a good relationship in society.